Combined effects of Er: YAG laser and casein phosphopeptide-amorphous calcium phosphate on the inhibition of enamel demineralization: An in vitro study - Sogra Yassaei; Neda Shahraki; Hossein Aghili; Abdolrahim Davari (Wolters Kluwer Medknow Publications, 2014)
Background: Development of white spot lesions on enamel is a significant and common problem during the fixed orthodontic treatment. Various preventive methods have been suggested. The purpose of this study was to evaluate the preventive potential of MI Paste Plus, Er: YAG Laser and combined under similar in vitro conditions against demineralization. Materials and Methods: In this experimental in vitro study, 60 extracted premolars were randomly allocated to four groups (n = 15) of control, MI Paste Plus, Laser and MI + Laser (MIL). Enamel surface of each group was treated with one of above materials before and during the pH cycling for 12 days through a daily procedure of demineralization and remineralization for 3 h and 20 h, respectively. Teeth were sectioned and evaluated quantitatively by cross-sectional microhardness testing at 20 μm intervals from the outer enamel surface toward dentinoenamel junction up to 160 μm and data were analyzed using the one-way analysis of variance and Tukey test. P < 0.05 was considered as significant. Results: MIL group had the least amount of demineralization (P < 0.001). Control group (C group) had the greatest relative mineral loss and the laser group (L group) had 45% less mineral loss than the C group and there was no significant difference between the MI Paste Plus and L group (P = 0.154) Conclusion: Based on these results, Er: YAG laser was able to decrease demineralization and was a potential alternative to preventive dentistry and was more effective when combined with casein phosphopeptide-amorphous calcium phosphate products.